Mothers' Reflections of Ambiguous Loss on Personal Family Functioning in Families with Children Who Have Autism Spectrum Disorders - EKŞİ, HALİL; ÇELİK AHBAB, HİLAL (ANKARA UNIV, FAC EDUCATIONAL SCIENCES, 2018)
The objective of this phenomenological study was to explore the impact of having a child with autism spectrum disorder (ASD) on mothers and its impact on their family relations. Using descriptive phenomenology design, 8 mothers were reached in the age range of 20-48 years and were interviewed for this study in 2010. Findings indicated that mothers perceived having a child with autism as an ambiguous loss. The sense of ambiguous loss was found to impair their emotional well-being and caused mood changes. This study has also provided evidence for the sense of ambiguous loss caused by autism to lead to structural and relational problems in family relationships. This study is one of the first studies to reveal that having a child with autism creates a sense of ambiguous loss and provides a basis for understanding its effects on the mother-child relationship, as well as the related effects on family relationships.
Keywords: Autism; ambiguous loss; family functioning; family relations; emotional well-being; INTELLECTUAL DISABILITY; SYNDROME SPECIFICITY; PARENTS; STRESS; IMPACT